Renewable Energy Microgrids to Improve Electrification Rate in Democratic Republic of Congo: Case of Hydro, Municipal Waste and Solar - Josue, Ngondo Otshwe; Mushi, Aviti Thadei (Tanzania Journal of Engineering and Technology, 2022)
Worldwide, it is imperative for citizens to have access to electrici-ty. This applies to Congolese--rural and urban dwellers, and if possible, it should be guaranteed by government ' s laws and poli-cies. However, the rural and urban areas of Democratic Republic of Congo (DRC) suffer majorly from lack of access to electricity. The major reasons are the high costs associated with connection to the national central grid and production insufficiency. There-fore, one feasible approach to electrify these areas is to use mi-crogrids. This technology is decent and viable option for energy revolution since it incorporates energy storage systems, distribut-ed generators, and localized loads. This paper has taken to im-plement this solution by firstly analysing some cities located at the borders of large rivers or watercourses (with known depth and width), such as the Congo River considered for hydrokinetic pow-er (HKP). However, where the Congo River does not pass through, the paper will consider largest rivers passing in the area. For the case of photovoltaic electricity production, large cities are considered those with good sunshine and large population who have purchasing power for the photovoltaic electricity. The waste to energy power plans will consider the top ten densely populated cities in DRC. The proposed microgrids will operate in isolation (islanded) mode. This paper proposed 44 projects to generate 795 690 kW total energy from the microgrids. These energies are divided as 661 000 kW from solar photovoltaic, 83 790 kW from waste to energy, and 50 900 kW from hydrokinetic generation. The urban share will be 94.9% and rural area share will be 5.1% of this generation. Further work needs to include biomass as a possible renewable energy to add in the mix. Keywords: Electricity deficit, Rural and urban electricity, Future isolated grid, Democratic Republic of Congo. Keywords: Electricity deficit, Rural and urban electricity, Future isolated grid, Democratic Republic of Congo.